2022
DOI: 10.1021/acsaelm.2c00023
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic Synapses with High Switching Uniformity and Multilevel Memory Storage Enabled through a Hf-Al-O Alloy for Artificial Intelligence

Abstract: Due to their high data-storage capability, oxidebased memristors with controllable conductance properties have attracted great interest in electronic devices for high integration density and neuromorphic synapses. However, high switching uniformity and controllable conductance of memristors during the conversion from a low (ON-state) to a high resistance state (OFFstate) have become essential for their implementation in neural networks. In this study, we fabricate a Pt/HfO 2 /HfAlO x /TiN memristor incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…Figure 6 d shows MNIST pattern recognition simulation results by using the conductance results of Fig. 6 b and c [ 70 , 71 ]. The result of using Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 d shows MNIST pattern recognition simulation results by using the conductance results of Fig. 6 b and c [ 70 , 71 ]. The result of using Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the effective size of the conductive filaments plays an important role to achieve various LRS values at different I CC or stop voltages ( V stop ). , When the electric field effect is strengthened, the homogeneity of the charge carrier distribution in the switching layer improves resulting in the generation of stronger CFs, hence obtaining a degradation in the LRS values . Herein, the perovskites/ITO films are characterized by the conductive AFM (C-AFM) measurement to observe the morphology of the CFs at distinct bias voltages (a Pt-coated probe as the top electrode and ITO as ground) (Figure a–d).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 When the electric field effect is strengthened, the homogeneity of the charge carrier distribution in the switching layer improves resulting in the generation of stronger CFs, hence obtaining a degradation in the LRS values. 36 Herein, the perovskites/ITO films are characterized by the conductive AFM (C-AFM) measurement to observe the morphology of the CFs at distinct bias voltages (a Pt-coated probe as the top electrode and ITO as ground) (Figure 4a−4d). As the positive bias voltage increases, the size and strength of the filaments are substantially improved (marked by green circles).…”
Section: Resultsmentioning
confidence: 99%
“…The technology of RRAMs is being advanced to realize high-density (feature size in the range of 10–50 nm), high-speed, and low-power devices. , RRAM devices have a wide variety of applications, in various fields, as NVM elements with longer retention times and as switches in digital logic systems for envisaging in-memory computation . The understanding of switching mechanisms , and the development of new methods to enhance switching speeds have been constantly evolving in recent times. , Based on the nature of switching mechanisms involved, these RRAM devices have also been used in neuromorphic systems , and as radiation detectors. Radiation detectors have traditionally been employed to sense the nature of radiation and to quantify the absorbed dose . Metal-oxide-semiconductor field effect transistor (MOSFET) devices were first identified to have potential for realizing electronic sensors for detecting the radiation.…”
Section: Introductionmentioning
confidence: 99%